A Comparative Study on the Renewable Energy Related Curriculums in the Universities in Guangdong- Hong Kong- Macao Greater Bay Area - Chung, Chao-Chen; Kaiqiang, Wang; Yujia, Zhong (Journal of Technology Innovations in Renewable Energy, 2023)
The development of energy professionals played important roles for energy innovation and sustainability transitions in Guangdong- Hong Kong- Macao Greater Bay Area. We selected three representative universities, i.e. Sun Yat-sen University, the Chinese University of Hong Kong, and the University of Macao in Guangdong, Hong Kong and Macao as the examples which presented current status of higher education in the fields of renewable energies. We compared these renewable energy related curriculums in terms of quantities, structures and contents. The results showed that the renewable energy related curriculums in the three universities should expand at postgraduate levels, strengthen their linkages with industries and increase interdisciplinary courses in order to optimize professional training in the Greater Bay Area.